The Implementation of Minister of Health Regulation Number 001 Year 2012 Concerning Individual Health Service Referral System for National Health Insurance Patients InBirobuli Public Health Center, Palu City (Medico Legal Update, 2021)
Central Sulawesi in 2018 showed the number of outpatient visits as much as 71.8%. The number of outpatientvisits to First Level Health Facilities with the highest percentage was Palu City with 711,394 cases. Thenumber of participants of the National Health Insurance in 2019 in Palu City was 476,968 thousand. Thehighest number of referrals in 13 public health centers in Palu City in 2019, namely the Birobulipublichealth center with the highest number of per quarter I 1384 and in the second quarter as many as 1172 cases.Type of Research is a qualitative case study approach. The research informants were 7 informants. Theresults showed that the communication variable between the implementers was quite good in implementingthe referral system but sometimes it was not consistent, there were no meetings or meetings to discussreference standards or referral issues. In terms of infrastructure, resources are good, there is still a lack ofmedical personnel, there is no training regarding referral standards. The Implementers’ attitude/dispositionand knowledge of medical personnel about the referral system are good. Standard Operational Proceduresalready exist but have not been socialized in every public health center.